2018
DOI: 10.1080/07448481.2018.1486844
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance literacy: A mixed methods study of college students

Abstract: Outreach and education for students should target specific deficits in knowledge such as those identified in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…For example, those with limited education are often found to have inadequate levels of HIL, yet studies with college students and young adults with high educational attainment, numeracy, and general literacy have been found to have inadequate functional HIL, (Nobles, Curtis, Ngo, Vardell, & Holstege, 2019; Tilley, Yarger, & Brindis, 2018). This emphasizes the need to better address the HIL needs of young adults, especially those who are entering the workforce, transitioning from their parent's health insurance plans, and/or making independent health insurance coverage decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, those with limited education are often found to have inadequate levels of HIL, yet studies with college students and young adults with high educational attainment, numeracy, and general literacy have been found to have inadequate functional HIL, (Nobles, Curtis, Ngo, Vardell, & Holstege, 2019; Tilley, Yarger, & Brindis, 2018). This emphasizes the need to better address the HIL needs of young adults, especially those who are entering the workforce, transitioning from their parent's health insurance plans, and/or making independent health insurance coverage decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Newly insured = α 0 +α 1 insured + α 2 usurious borrowing + α 3 ill + Xβ + u (1) non-usurious borrowing = μ 0 + μ 1 newly insured +Xγ+ v (2) Where, newly insured, insured, usurious borrowing, non-usurious borrowing, and ill are dummy variables that capture whether a decision to be newly insured was taken, whether or not the household was already insured, whether or not a household engaged in usurious borrowing, whether or not a household engaged in non-usurious borrowing, and whether or not a household saw illness in the family in a recent past. X is a vector of covariates (including education level) associated with the coefficient vectors β and γ in regressions (1) and (2). u and v are stochastic error terms.…”
Section: Results Of the Regression Analysismentioning
confidence: 99%
“…The lack of a feeling of necessity (noted at the very end of the previous quote), often presents itself as a hindrance to insurance buying. For example, in a recent study, 2 it is observed that half the respondents indicated confusion about their health insurance plans, often leading to the delay or a complete foregoing of medical care. Therefore, targeted outreach and education programmes for buyers of insurance products are often recommended to fill in these 'knowledge deficits. '…”
Section: Key Messagesmentioning
confidence: 99%
See 2 more Smart Citations